TIPOLOGI FATWA DI ERA MODERN: DARI OFFLINE KE ONLINE - Rusli Rusli (Hunafa: Jurnal Studia Islamika, 2011)
This paper deals with the typology of fatwā (Islamic legal opinion) in a contemporary era. It is assumed that change of paradigm will give an impact to changes in knowledge and its media of transmission. This also applies to fatwā. Due to this change of paradigm, fatwā has also undergone changes either in content or media of transmission. In this globalization era, which is characterized with the advance of information technology, fatwā can be divided into such categories as state, personal, individual, collective, and online fatwās. These fatwa models have their own unique characteristics in terms of ideologies, interests and scope of transmission.